Impact of intraoperative goal-directed fluid therapy on major morbidity and mortality after transthoracic oesophagectomy: a multicentre, randomised controlled trial - Mukai, Akira; Suehiro, Koichi; Watanabe, Ryota; Juri, Takashi; Hayashi, Yasue; Tanaka, Katsuaki; Fujii, Takashi; Ohira, Naoko; Oda, Yutaka; Okutani, Ryu; Nishikawa, Kiyonobu (British journal of anaesthesia : BJA, 2020)
Transthoracic oesophagectomy is associated with major morbidity and mortality, which may be reduced by goal-directed therapy (GDT). The aim of this multicentre, RCT was to evaluate the impact of intraoperative GDT on major morbidity and mortality in patients undergoing transthoracic oesophagectomy. Adult patients undergoing transthoracic oesophagectomy were randomised to receive either minimally invasive intraoperative GDT (stroke volume variation <8%, plus systolic BP maintained >90 mm Hg by pressors as necessary) or haemodynamic management left to the discretion of attending senior anaesthetists (control group; systolic BP >90 mm Hg alone). The primary outcome was the incidence of death or major complications (reoperation for bleeding, anastomotic leakage, pneumonia, reintubation, >48 h ventilation). A Cox proportional hazard model was used to examine whether the effects of GDT on morbidity and mortality were independent of other potential confounders. A total of 232 patients (80.6% male; age range: 36–83 yr) were randomised to either GDT (n=115) or to the control group (n=117). After surgery, major morbidity and mortality were less frequent in 22/115 (19.1%) subjects randomised to GDT, compared with 41/117 (35.0%) subjects assigned to the control group {absolute risk reduction: 15.9% (95% confidence interval [CI]: 4.7–27.2%); P=0.006}. GDT was also associated with fewer episodes of atrial fibrillation (odds ratio [OR]: 0.18 [95% CI: 0.05–0.65]), respiratory failure (OR: 0.27 [95% CI: 0.09–0.83]), use of mini-tracheotomy (OR: 0.29 [95% CI: 0.10–0.81]), and readmission to ICU (OR: 0.09 [95% CI: 0.01–0.67]). GDT was independently associated with morbidity and mortality (hazard ratio: 0.51 [95% CI: 0.30–0.87]; P=0.013). Intraoperative GDT may reduce major morbidity and mortality, and shorten hospital stay, after transthoracic oesophagectomy. UMIN000018705